ClicaBrasil Portuguese Language and Culture for Intermediate Students - Flanzer, Vivian (Open textbook library., 2019)
ClicaBrasil was developed for intermediate level Portuguese language courses at UT-Austin. People all ove the world are now using it for different purposes: self-study, classroom instruction, tutoring, or as a pastime.The lessons in ClicaBrasil integrate reading, writing, listening and reading comprehension, grammar, vocabulary, oral communication, and cultural activities. Numerous video clips (157, to be precise!) that show different Brazilians speaking about their lives, their culture, and their country support and enhance these activities.